Ablation behavior of three-dimensional Cf/SiC-ZrC-ZrB2 composites prepared by a joint process of sol-gel and reactive melt infiltration. (15th April 2018) - Chen, Xiaowu; Feng, Qian; Zhou, Haijun; Dong, Shaoming; Wang, Jingxiao; Cao, Yanpeng; Kan, Yanmei; Ni, Dewei
Highlights: Ablation behavior of Cf /SiC-ZrC-ZrB2 under air plasma was studied. SiO2 -ZrO2 -B2 O3 oxide scale played a predominant role during the ablation. <2000 °C, composites showed negative recession due to passive oxidation of SiC. >2000 °C, composites showed positive recession due to active oxidation of SiC. Abstract: Three-dimensional Cf /SiC-ZrC-ZrB2 composites were fabricated by a joint process of sol-gel and reactive melt infiltration. Ablation test of the composites was performed under air plasma. The composites showed negative recession rates at 1800–2000 °C, while positive recession rates above 2000 °C. Results revealed that dense SiO2 -ZrO2 -B2 O3 layer formed on the sample surface prevented the ablation process extending inward the samples. At higher temperature, active oxidation of SiC and severe evaporation of oxide phase significantly impaired the integrity of the oxide layer and inevitably deteriorated the resistance of the oxide layer to the air plasma.